Case report: Prenatal diagnosis in the fetus of a couple with both thalassemia and deafness genes - Li, Youqiong; Liang, Liang; Bai, Jinping; Zheng, Lihong; Qin, Ting (Frontiers in Genetics, 2023)
Background: Prenatal diagnosis and genetic counseling play an important role in preventing and controlling birth defects. No reports were found of prenatal diagnosis of couples carrying both the thalassemia and deafness genes. In this study, we presented the prenatal screening and diagnosis of a couple with both thalassemia and deafness genes, contributing to better genetic counseling.Case Report: A couple visited our hospital for a routine prenatal examination. As required by the policy in our region, they underwent screening and genetic diagnosis for thalassemia. Meanwhile, they did not accept the recommendation to test for SMA and deafness genes. The female was confirmed to be a Hb Quong Sze (Hb QS) carrier (αQSα/αα, βN/βN), and the male had Hb H disease combined with β-thalassemia (--SEA/αCSα, βCDs41-42(-TTCT)/βN). A prenatal diagnosis of the fetus revealed a Hb CS heterozygote. Subsequent complementary testing showed that the male was a double heterozygote of the GJB2 gene c.299_300delAT combined with c.109G＞A, and Sanger sequencing confirmed that the female was a carrier of c.508_511dup in the GJB2. Fortunately, the chorionic villi results indicated that the fetus was only a carrier of deafness.Since both partners carried thalassemia and deafness genes, the couple required prenatal diagnosis for the respective mutations. Expanded carrier screening (ECS) is a more advanced technology that can detect multiple disease genes simultaneously.